PID Controller for Optimum Energy Efficiency in Air-Conditioner - Shahir, Ashman; Oktaviandri, Muchamad (International Journal of Electrical, Energy and Power System Engineering, 2022)
Air conditioning is a process of excluding moisture and heat in interior space for better thermal comfort. It is also one of the largest energy consumers in a household. The air-conditioner uses a lot of energy to maintain desired room temperature. The world is getting old and technologies are getting more advanced every day, energy-efficient appliances are needed to preserve the world. This paper presents a design and testing of the PID control for temperature and humidity control using Arduino to get the optimum energy efficiency. The system was developing by implementing the DHT22 sensor. The objectives of this work are; to design experimental model of air conditioning system, and to optimize the system using PID control. The Arduino is used in this work to showcase the temperature and humidity reading. The experimental model has been successfully built for use with PC fan with 12V and 0.26A current rate. The real-life performance is quite satisfactory.